Analisis Keamanan Aplikasi “Point of Sale” Berbasis Web Menggunakan Pendekatan ISO/IEC 29119 Software Testing Standard - Nurhasan; Fariz Nurrahim; Aprien Febrian; Chairul Anwar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Web-based Point of Sale (POS) systems are widely adopted by small and medium-sized retail businesses, yet insufficient security implementation can expose them to data breaches and financial losses. This study analyzes security vulnerabilities in the Codekop POS v2.0 application using a testing framework based on the ISO/IEC 29119 standard. The testing process follows ISO/IEC 29119-2 with documentation aligned to ISO/IEC 29119-3, applying manual code review techniques to ten core components. The assessment focuses on authentication, session management, injection, cross-site scripting (XSS), cross-site request forgery (CSRF), and directory traversal, referring to the OWASP Top 10 guidelines. The results reveal one critical, four high, five medium vulnerabilities, and four aspects meeting security standards, with an overall compliance rate of 26.7%. This study provides an ISO/IEC 29119-based web application security testing framework and prioritized improvement recommendations to strengthen POS system security.